1794 R.I. Pub. Laws 21, An Act To Organize The Militia Of This State, § 10 - (:unkn) unknown (General Publisher, 1794)
That every Corporal who shall neglect to warn the Men to appear at every Rendezvous mentioned in this Act, when thereunto required as aforesaid without sufficient excuse, shall forfeit the Sum of Twelve Shillings, Lawful Money: That every non-commissioned officer or private who shall neglect to appear at the regimental Rendezvous, shall forfeit the sum of Six Shillings and for every day he shall neglect to appear at the company parade, he shall forfeit Four Shillings and Sixpence. And if he shall not be armed and equipped according other said Act of congress, when so appearing, without sufficient excuse, he shall, for appearing without a gun, forfeit one shilling and sixpence; without bayonet and belt six pence; without a Bayonet and Belt, Sixpence; without a Cartouch-Box and Cartridges, Sixpence. . .
--
Keywords: ARMED FORCES